Dinamika Aktor dalam Forum Komunikasi Tanggung Jawab Sosial Perusahaan di Kabupaten Tuban - Bedhah Adityo Nugroho; Janianton Damanik (Department of Social Development and Welfare, Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2020)
The divergent of actors within communicaton forum influence the changing of institution’s characters and escalate the interest contestation. The objective of this study is elucidating the dynamic relations and interaction among actors under the authoritative organization in Tuban district. This article employed qualitative method which uses literatures, documentations, observations, and in-dept interviews. The latest method relies on eleven central informants that represent company, country, and society who have relation with CSR Communication Forum in Tuban. Th result shows that the main actor who initiate the emergence of CSR Communication Forum is country, thus affect the nature of institution which more instructive (top-down) and state-centric. The local government is dominating the forum and other actors use the local regulation to produce dependency of company to country. In addition, shifting of power from regulation based to interest based create institution dilemma, institution disorientation and competition of resources among actors. Although using CSR governance, the political dynamics and institution development have not achieved its optimum result.